Covid-19 X-ray image classification using SVM based on local binary pattern - DURU, ADİL DENİZ (My University, 2021)
© 2021 IEEE.Coronavirus usually transmits from the animal to the human, but now, the virus transmission is between persons. Therefore, scientists and researchers are trying to develop several types of machine learning methods to defend against COVID-19. Medical images play a significant role in this time due to they can be used to recognize COVID-19 accurately. However, in this paper, we used X-Ray images, the images undergone to sharpening techniques to increase the results further. The texture techniques named local binary pattern (LBP) have been used in order to extract features. The features obtained were applied to the support vector machine (SVM). The results we achieved were 100% for all performance measurements. Our results were conspicuously superior compared to the state-of-the-art papers published.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Kütüphanecilik; Harita Mühendisliği-Geomatik; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Bilgisayar Bilimleri; Algoritmalar; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Library Sciences; Geotechnical Engineering; Information Systems, Communication and Control Engineering; Control and System Engineering; Computer Sciences; algorithms; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Bilgisayar Bilimi; Mühendislik; Sosyal Bilimler Genel; OTOMASYON & KONTROL SİSTEMLERİ; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; TELEKOMÜNİKASYON; ALETLER & GÖSTERİM; MÜHENDİSLİK, MULTİDİSİPLİNER; MÜHENDİSLİK, ÜRETİM; BİLGİ BİLİMİ VE KÜTÜPHANE BİLİMİ; Engineering, Computing & Technology (ENG); Social Sciences (SOC); COMPUTER SCIENCE; ENGINEERING; SOCIAL SCIENCES, GENERAL; AUTOMATION & CONTROL SYSTEMS; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; TELECOMMUNICATIONS; INSTRUMENTS & INSTRUMENTATION; ENGINEERING, MULTIDISCIPLINARY; ENGINEERING, MANUFACTURING; INFORMATION SCIENCE & LIBRARY SCIENCE; Medya Teknolojisi; Fizik Bilimleri; Kontrol ve Optimizasyon; Enstrümantasyon; Emniyet, Risk, Güvenilirlik ve Kalite; Yapay Zeka; Bilgisayar Ağları ve İletişim; Bilgisayar Bilimi Uygulamaları; Bilgi Sistemleri ve Yönetimi; Sosyal Bilimler ve Beşeri Bilimler; Media Technology; Physical Sciences; Control and Optimization; Instrumentation; Safety, Risk, Reliability and Quality; Artificial Intelligence; Computer Networks and Communications; Computer Science Applications; Information Systems and Management; Social Sciences & Humanities